2017
DOI: 10.1186/s13104-017-3087-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry reference intervals for healthy elderly population in Asmara, Eritrea

Abstract: ObjectiveThere is a scarcity of reference interval studies on the elderly in Africa. This study establishes reference interval for the elderly for some commonly used biochemical parameters. In this study, 255 conveniently sampled, healthy elderly, participants meeting Clinical and Laboratory Standards Institute (CLSI C28-A3) guidelines were enrolled. The results obtained may have utility in clinical diagnosis, patient management and research.ResultsIn general, the consensus reference interval established in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
4
12
1
Order By: Relevance
“…Out of 7,797 volunteers, a total of 1,628 were excluded. According to CLSI and IFCC recommendations, studies aimed at establishing Reference Intervals should have a minimum of 120 healthy participants in each category of the grouping variable [ 3 , 13 ]. With the enrolment of 5932 males and 237 females, this requirement was exceeded in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Out of 7,797 volunteers, a total of 1,628 were excluded. According to CLSI and IFCC recommendations, studies aimed at establishing Reference Intervals should have a minimum of 120 healthy participants in each category of the grouping variable [ 3 , 13 ]. With the enrolment of 5932 males and 237 females, this requirement was exceeded in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Research studies find [2][3][4][5] RIs are with variety of factors involved such as race, region, ethnicity, diet, and so on. For example, Wu et al [6] found that lower limit of the platelet interval in Chinese Han adults was slightly lower than that of the peer group in the United States [7] and Malaysia [8], and RIs of white blood cell count and neutrophil count were lower than those of the homologous US population [7] while higher than those of the Africans [9]; Oliver's research [10] showed that RIs of certain biochemical indicators of the aged living in Asmara, Eritrea, were higher than those of Caucasians and lower than those of South Africans. For example, the actual upper limit of total bilirubin was 2 times higher than it was recommended by the Eritrean Ministry of Health; the median of creatine kinase (CK) activity of healthy black adults was about twice higher than Caucasians in both sexes [11].…”
Section: Introductionmentioning
confidence: 97%
“…Nigerian public health laboratories, like most clinical laboratories in Africa, rely on reference intervals obtained from textbooks, instrument manuals and reagent inserts for interpretation of laboratory results [8,9,13,14]. This study has shown decreased lower reference limits and higher upper limits with wider overall reference intervals for most of our study analytes when compared to western values.…”
Section: Discussionmentioning
confidence: 74%